Exogenously Applied Proline Enhances Morph-Physiological Responses and Yield of Drought-Stressed Maize Plants Grown Under Different Irrigation Systems - Ibrahim, Abd El-Aty; Abd El Mageed, Taia; Abohamid, Yasmin; Abdallah, Hanan; El-Saadony, Mohamed; AbuQamar, Synan; El-Tarabily, Khaled; Abdou, Nasr (Frontiers in Plant Science, 2022)
The exogenous application of osmoprotectants [e.g., proline (Pro)] is an important approach for alleviating the adverse effects of abiotic stresses on plants. Field trials were conducted during the summers of 2017 and 2018 to determine the effects of deficit irrigation and exogenous application of Pro on the productivity, morph-physiological responses, and yield of maize grown under two irrigation systems [surface irrigation (SI) and drip irrigation (DI)]. Three deficit irrigation levels (I100, I85, and I70, representing 100, 85, and 70% of crop evapotranspiration, respectively) and two concentrations of Pro (Pro1 = 2 mM and Pro2 = 4 mM) were used in this study. The plants exposed to drought stress showed a significant reduction in plant height, dry matter, leaf area, chlorophyll content [soil plant analysis development (SPAD)], quantum efficiency of photosystem II [Fv/Fm, Fv/F0, and performance index (PI)], water status [membrane stability index (MSI) and relative water content (RWC)], and grain yield. The DI system increased crop growth and yield and reduced the irrigation water input by 30% compared with the SI system. The growth, water status, and yield of plants significantly decreased with an increase in the water stress levels under the SI system. Under the irrigation systems tested in this study, Pro1 and Pro2 increased plant height by 16 and 18%, RWC by 7 and 10%, MSI by 6 and 12%, PI by 6 and 19%, chlorophyll fluorescence by 7 and 11%, relative chlorophyll content by 9 and 14%, and grain yield by 10 and 14%, respectively, compared with Pro0 control treatment (no Pro). The interaction of Pro2 at I100 irrigation level in DI resulted in the highest grain yield (8.42 t ha–1). However, under the DI or SI system, exogenously applied Pro2 at I85 irrigation level may be effective in achieving higher water productivity and yield without exerting any harmful effects on the growth or yield of maize under limited water conditions. Our results demonstrated the importance of the application of Pro as a tolerance inducer of drought stress in maize.